I600 from the CSR test as a measure of pilot oven coke strength. (7th February 2020) - Koval, Lukas; Sakurovs, Richard; Hockings, Kim
ABSTRACT: In this study, I600 test results were compared with conventional drum indices. The I600 test is equivalent to the CSR I-drum test without pre-reaction of coke with CO2 . The aim of this study was to determine to what extent the results of the I600 test could provide a useful indicator of the results of the commonly used coke strength indices. It was found that I600 correlated best with indices which had most similar particle size and drum revolutions. Further, significant improvement of relationship between CSR and CRI was obtained by incorporating the I600 index into the regression. Moreover, it was found that charge bulk density not only affected the values for the conventional drum indices, but it also affected the relationship between them and I600 . Thus, charge bulk density must be included in regression aiming to compare drum indices especially those comparing results from tests with different number of drum revolutions.